Business Inteligence aplicada na metodologia Peer Instruction na plataforma Be Active - Vargas, Vinícius Fagundes (2024)
This multidisciplinary master's research in Education wasdeveloped within the Graduate Program in Education (PPGE) at the Universidade do Oeste Paulista (Unoeste) in Research Line 01: Public Policies in Education, formative processes, and diversity. Technological advancement has played a fundamental role in transforming various sectors, including education. In the educational context, the Be Active platform supports several active teaching methodologies, one of which is the Peer-Instruction methodology. Peer-Instruction is an active methodology created by Eric Mazur, a Physics professor at Harvard University. It was designed to promote student discussion and encourage problem-solving and conceptual understanding rather than focusing solely on memorization. This study focused on the application of Business Intelligence (BI) with the aid of the Power BI tool to explore data collected from this module, aiming to provide visualization models for teachers related to student performance in terms of participation in PI events. Business Intelligence, or BI, is a set of processes and tools used to collect, analyze, and transform data into meaningful information. The Power BI tool stood out as a powerful solution in this context, allowing for the creation of interactive analyses and custom reports. The research aimed to extract insights from the data collected in the Peer-Instruction module of Be Active. This included the analysis of student participation, individual and group performance, as well as the attempts for each question. By using Power BI, the data were transformed into dynamic visualizations that will assist teachers in making educational decisions related to student performance in the active methodology Peer-Instruction events. The methodology employed in this research encompassed both qualitative and quantitative approaches. This approach combined the collection of bibliographic data from sources such as books, scientific articles, dissertations, and theses. Therefore, this research sought to leverage Business Intelligence concepts with the use of Power BI to enhance the decision-making process in the context of the Peer-Instruction module of the Be Active platform. By exploring the data collected in the Peer-Instruction module and presenting visualization models, the goal is to improve the quality of education, promoting a more personalized approach to teaching.